Gender-Specific Effects of Import Competition on Individual Fertility Decisions - Andreea A. Piriu (Global Labor Organization (GLO), 2020)
This paper studies the effects of import competition from China and Eastern Europe (EE) on the fertility decisions of individuals in German manufacturing. Through the lens of gender, the paper uniquely contributes to the literature by linking import competition to longitudinal individual data to examine individual fertility. Two separate measures of import exposure are computed for competition from China and EE (amassing five countries), whose trade volumes with Germany have increased remarkably during the panel years. Fixed-effects instrumental variable (FEIV) estimation results show that individual fertility decreases by 1.6 p.p. and by 2.0 p.p. with rising competition from China and EE, respectively. The effects are robust and consistent across different subgroups of individuals. Effects of import competition are then inspected by gender, alongside potential mechanisms underlying fertility decisions. Both male and female workers' fertility is affected via reduced earnings, though differently. The effect on male fertility is negative, with shortened employment duration. Conversely, the effect on female workers' fertility is positive, with worsened working conditions. Furthermore, in line with family economics theory, these results suggest that there is a substitution effect in the labour supply of women, here prevalently concentrated in low-technology sectors: as female earnings fall and their opportunity cost of work is lower, the prospect of having children possibly becomes a more rewarding alternative.
Keywords: F14; F16; J11; J13; J16; 330; trade-induced shocks; labour market conditions; import competition; individual fertility; female labour supply; FEIV estimation; Germany